PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA RUMAH MAKAN AYAM PENYET MUGO MULYO KARAWANG JAWA BARAT - Misbahul Munir; Junengsih Junengsih; Supriydi Supriydi (JURNAL ILMIAH EDUNOMIKA, 2024)
Marketing is an effort to meet consumer needs through creating products and/or services which are then enjoyed or purchased by those who need them through an exchange process that must be fulfilled by a company in order to be successful in achieving the goal of creating consumers and retaining customers. There is a problem formulation, namely what is the quality of the product, what is the purchasing decision and how much influence does product quality have on purchasing decisions. The aim of this research is to find out the formulation of the problem, this research method is quantitative with the population, namely consumers at the penyet mugo mulyo chicken restaurant, with a sample of 60 respondents. With a sampling technique using a quota sampling technique. The results of the research were that the positive influence was very strong, obtaining an r value of 0.836 and providing a contribution of 69.9%. on product quality on purchasing decisions.